2019
DOI: 10.1101/538439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contextual cues as modifiers of cTBS effects on indulgent eating

Abstract: Background: Prior studies have found that continuous theta burst stimulation (cTBS) targeting the left dlPFC results in reliable increases in consumption of calorie-dense food items. However, it is not known to what extent such effects are modified by cues in the immediate eating environment. Tempting environments (i.e., those saturated with appetitive eating cues) may lead to more reliance on cognitive control networks involving the dlPFC, thereby enhancing cTBS on eating.Objective/Hypothesis: The objective w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Together, these results suggest that GDM-induced changes in cortical GMV may be associated with both current and future weight status. While the functional significance of GDM exposure-associated alterations in cortical GMV remains to be established, we can reasonably speculate that functional deficits in cortical areas implicated in dietary self-regulation may lead to greater adiposity in children exposed to GDM given that 1) cortical regions, particularly the MFG, play a critical role in self-regulation, including top down regulation of craving and food consumption(53, 54); and 2) smaller cortical GMV in prefrontal areas has been shown to be associated with poorer self-regulation(55), which is tightly linked to overeating and obesity(56). Additional studies using the ABCD dataset found other neural correlates of obesity or weight gain, including lower cortical thickness (primarily in the prefrontal cortex)(57) and higher cell density in the nucleus accumbens(58).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these results suggest that GDM-induced changes in cortical GMV may be associated with both current and future weight status. While the functional significance of GDM exposure-associated alterations in cortical GMV remains to be established, we can reasonably speculate that functional deficits in cortical areas implicated in dietary self-regulation may lead to greater adiposity in children exposed to GDM given that 1) cortical regions, particularly the MFG, play a critical role in self-regulation, including top down regulation of craving and food consumption(53, 54); and 2) smaller cortical GMV in prefrontal areas has been shown to be associated with poorer self-regulation(55), which is tightly linked to overeating and obesity(56). Additional studies using the ABCD dataset found other neural correlates of obesity or weight gain, including lower cortical thickness (primarily in the prefrontal cortex)(57) and higher cell density in the nucleus accumbens(58).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies would benefit from exploring the range of mPFC stimulation effects that could be produced in inhibitory or facilitating eating environments, and using different variants of TBS protocols (e.g., cTBS). Such studies focussing on the dlPFC have produced interesting findings (Safati and Hall, 2019), and could provide a template for further research involving the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have reported that in attractive environments (i.e. those full of appetizing food cues), the provision of contextual cues of convenience could cause individuals to intensify intentional food preferences in daily life through cognitive control failure, resulting in a rapid increase in the consumption of calorie-intensive food (Safati and Hall, 2019). In the long run, this will exacerbate the risks of public health and disease control.…”
Section: Theoretical and Practical Significancementioning
confidence: 99%